Analysis of Factors Causing High Non-Specialized Referral Ratio of Inpatient Primary Health Centers - Rizki Fadila; Alifia Firda Purnomo (STIKes Hang Tuah Pekanbaru, 2021)
As part of the quality control and cost control system in health services, the provision of health services to JKN participants must be carried out in stages according to medical indications. The fact shows that the Puskesmas has not carried out its function as a gatekeeper properly due to the high number of referrals, especially for non-specialist services. The purpose of this study was to obtain an overview of the causes of the high ratio of non-specialist referrals at the Pasuruan District Health Center. This research is a quantitative descriptive study with a cross sectional research design. The research sample was 4 inpatient health centers with a non-specialist referral ratio > 2% in Pasuruan Regency. The results showed that the most frequently referred disease was insulin-dependent diabetes mellitus. All inpatient health centers with a high ratio of non-specialist referrals do not have complete facilities and infrastructure according to standards. In addition, as many as 75% of Puskesmas do not have type of health worker based on Permenkes 43 of 2019. In this case, local governments must always strive the needs of facilities, infrastructure and health workers, so that puskesmas can provide excellent health services.